Global myocardial work parameters measured by the index beat method are comparable to the average of 10 beats in patients during atrial fibrillation - Kong, Ling-Yun; Wang, Xiu-Juan; Chen, Ling-Ling; Xiang, Wei; Liu, Fang (Frontiers in Cardiovascular Medicine, 2025)
IntroductionEvaluation of left ventricular (LV) global systolic function is clinically important for patients with atrial fibrillation (AF); however, the rhythm irregularity inherent to AF poses challenges for assessing novel LV systolic function parameters, such as global myocardial work (MW). This study aimed to validate the feasibility of using the single index beat method to quantify LV MW during echocardiography in patients with AF, compared with the traditional 10-beat average method.MethodsA prospective study was performed in 120 patients with AF at the time of the index echocardiography. Global longitudinal strain was assessed using speckle tracking echocardiography from a triplane dataset, followed by MW analysis to calculate global myocardial work index (GWI), global constructive work (GCW), global wasted work (GWW), and global work efficiency (GWE). A total of 10 consecutive beats were evaluated, with both the average value and the maximal difference among the 10 beats recorded. The index beat was defined as on in which the ratio of the preceding to the pre-preceding R-R interval was approximately 1 (0.96–1.04). MW parameters from the index beat were extracted for analysis. Inter-method consistency was assessed using the intra-class correlation coefficient (ICC) with a single-rater, absolute agreement, two-way random effects model. Inter- and intra-observer reproducibility was also assessed.ResultsGlobal MW derived from the index beat was comparable with the average of 10 beats: GWI, 1,157.19 ± 416.83 vs. 1,188.98 ± 452.96 mmHg% (p < 0.05); GCW, 1,721.46 ± 524.69 vs. 1,732.46 ± 524.24 mmHg% (p > 0.05); GWW, 237.95 (183.60) vs. 207.50 (207.25) mmHg% (p < 0.001); and GWE, 85.80% (11.05) vs. 86.50% (12.75) (p < 0.001). Consistency analysis showed that ICCs for all assessed MW parameters were >0.87. Satisfactory inter- and intra-observer reproducibility of the measurements by the index beat method was also found.ConclusionsGlobal MW measured using the index beat method demonstrated good agreement with the average over 10 beats in patients with AF, supporting its reliability as a surrogate for the traditional method in clinical practice.